Integrative Strategies for Preventing and Managing Metabolic Syndrome: The Impact of Exercise and Diet on Oxidative Stress Reduction—A Review - Ana Onu; Daniela-Marilena Trofin; Andrei Tutu; Ilie Onu; Anca-Irina Galaction; Dragos-Petrica Sardaru; Dan Trofin; Cristiana Amalia Onita; Daniel-Andrei Iordan; Daniela-Viorelia Matei (Life)
Metabolic syndrome (MetS) is characterized by central obesity, insulin resistance, hypertension, dyslipidemia, and chronic inflammation, significantly increasing the risk of cardiovascular disease and type 2 diabetes. Effective management of MetS is critical, with exercise being a key intervention. This review analyzed the effects of different exercise intensities—low, moderate, and high-intensity interval training (HIIT)—on metabolic health, oxidative stress (OS), inflammation, and cardiovascular function. A search of Medline, PEDro, and EBSCO identified 2251 articles, with 159 studies published between 1999 and 2025 included after screening. Low-intensity exercise improved insulin sensitivity, reduced OS markers (e.g., MDA, 8-OHdG), and enhanced antioxidant enzyme activity. Moderate-intensity exercise showed similar benefits with notable reductions in inflammatory markers (e.g., IL-1β, TNF-α). HIIT promoted fat loss and improved metabolic markers but temporarily increased OS and inflammation. Dietary strategies also play a critical role. The Mediterranean diet and Dietary Approaches to Stop Hypertension (DASH) diets are well established, emphasizing nutrient-dense foods like unsaturated fats and fiber to reduce inflammation and manage weight. The ketogenic diet (KD), a high-fat, low-carbohydrate approach, has recently gained attention for its metabolic benefits. KD induces ketosis, improving insulin sensitivity, reducing triglycerides, and enhancing fat oxidation. Studies show KD effectively reduces body weight and glucose levels, though long-term adherence and nutrient deficiencies remain challenges. Intermittent fasting also showed potential benefits, though effects on glucose metabolism were inconsistent. This review underscores the need for tailored approaches combining exercise, diet, and fasting to optimize MetS outcomes, offering integrative strategies for prevention and management.